Dampak Oforektomi terhadap Kualitas Hidup dan Fungsi Seksual Orang dengan Kanker Payudara - Fuadi, Hasan; Afiyanti, Yati; Gayatri, Dewi (Journal of Telenursing (JOTING), 2024)
This study aims to identify the impact of orthorectomy on breast cancer patients, especially on their quality of life and sexual function. We conducted a systematic review adhering to PRISMA guidelines, searching articles from PubMed, ProQuest, Embase, and ScienceDirect databases from inception to March 2024. The search terms used were "oophorectomy", "quality of life", "sexual function", and "breast cancer". Results from 8 articles showed that oophorectomy can negatively affect quality of life, especially in physical and psychosocial aspects, and can be associated with sexual dysfunction. Ophorectomy was also associated with significant reductions in all-cause mortality and breast cancer-specific mortality. In conclusion, this study shows about ooforectomy have a significant impact on quality of life and sexual function of women, especially on physical and psychosocial aspects. Although, these impacts do not entirely affect quality of life, Keywords: Oophorectomy, Breast Cancer, Quality of Life, Sexual Dysfunction